MATHEMATICS AS A PHILOSOPHICAL FOUNDATION IN HOMBO BATU: EXPLORING NIAS' LOCAL WISDOM THROUGH THE PERSPECTIVE OF MATHEMATICS - Harefa, Darmawan (Universitas Nias Raya, 2025)
This study aims to explore the relationship between mathematics and local wisdom through the traditional game of Hombo Batu in Nias. Hombo Batu, which is a part of Nias culture, contains mathematical concepts that can be used to understand basic mathematical principles in the context of local culture. This library research identifies how concepts such as symmetry, measurement, and patterns are found in this game, as well as how the philosophical values embedded in Hombo Batu, such as cooperation, accuracy, and bravery, can be linked to the mathematical concepts taught in schools. Through the perspective of mathematics, this game serves as an effective medium to teach mathematical concepts in an applied, relevant, and contextual manner for students. This study concludes that the integration of mathematics with local culture can enrich the learning experience, enhance students' understanding of mathematics, and strengthen their cultural identity. Therefore, Hombo Batu can be used as a tool to teach mathematics within a broader cultural context.